Phytochemical Screening, Physicochemical Properties, Acute Toxicity Testing and Screening of Hypoglycaemic Activity of Extracts of Eremurus himalaicus Baker in Normoglycaemic Wistar Strain Albino Rats. (29th April 2014) - Mushtaq, Ahlam; Akbar, Seema; Zargar, Mohammad A.; Wali, Adil F.; Malik, Akhtar H.; Dar, Mohammad Y.; Hamid, Rabia; Ganai, Bashir A.
Abstract : In the present study EtOAc, MeOH, and aqueous extracts of Eremurus himalaicus were evaluated for hypoglycaemic effect in normal rats using both oral glucose tolerance test and 14-day oral administration study. Phytochemical and physicochemical screening was also done. In oral glucose tolerance test the aqueous and MeOH extracts of Eremurus himalaicus at a dose level of 500 mg/kg body weight prior to glucose load resulted in a significant fall in blood glucose level within 150 min. of glucose administration. The aqueous extract at a dose level of 250 mg/kg body weight and 500 mg/kg body weight also showed good hypoglycaemic response ( P < 0.001); this was followed by MeOH extract at a dose level of 500 mg/kg body weight ( P < 0.05), while MeOH extract at dose level of 250 mg/kg body weight and ethyl acetate extract at dose level of 250 mg/kg body weight and 500 mg/kg body weight exhibited insignificant effect. Phytochemical screening of extracts revealed the presence of alkaloids, terpenoids, phenolics, tannins, saponins, cardiac glycosides, and flavonoids. The results indicate that aqueous extract possess significant hypoglycaemic activity in normoglycaemic rats which may be attributed to the above-mentioned chemical constituents.